OP0262 Similar Clinical and Radiological Outcome in The Cobra and Cobra-Light Treatment Group 4 Years after Initiation of The Cobra-Light Trial. (15th July 2016) - Konijn, N.; van Tuyl, L.; Boers, M.; den Uijl, D.; ter Wee, M.; Kerstens, P.; Voskuyl, A.; van Schaardenburg, D.; Nurmohamed, M.; Lems, W.
Abstract : Background: COBRA and COBRA-light combination therapy are equally effective treatments for early rheumatoid arthritis (RA) after 26 and 52 weeks [1, 2], but the long-term effect of start with COBRA-light therapy is unknown. Objectives: To investigate the efficacy of initial COBRA and COBRA-light combination therapy after a 4 year follow-up period. A detailed analysis of long-term safety will be presented separately. Methods: In the COBRA-light trial, 164 patients with recent-onset RA were randomized to either COBRA (prednisolone 60 mg/day, tapered to 7.5 mg/day in 6 weeks; MTX 7.5 mg/week and sulfasalazine 2 g/day; n=81) or COBRA-light therapy (prednisolone 30 mg/day, tapered to 7.5 mg/day in 8 weeks and MTX escalated to 25 mg/week in 8 weeks; n=83). In the period of 26 to 52 weeks; treatment intensification of MTX and addition of etanercept was protocollized (treat-to-target). After 52 weeks, treatment was continued without protocol. Four years after trial initiation, all patients who had initiated therapy (n=162) were invited to participate in the COBRA-light extension study. Main outcomes were: Disease Activity Score in 44 joints (DAS), Health Assessment Questionnaire (HAQ), Sharp – Van der Heijde radiographic Score (SHS) and ACR/EULAR Boolean remission. Longitudinal mixed modeling (DAS), TOBIT (HAQ), and GEE analyses (SHS: log negative binomial; Boolean remission: logit binomial) were performed in STATA. Results: A total of 149 out of 162 original trial patients participated in the extension study (77 COBRA and 72 COBRA-light patients); 2 COBRA vs. 3 COBRA-light patients had died, 1 vs. 5 patients were not able or willing to participate, and 1 vs. 1 patient were in drug-free remission and out of care. After the 52 weeks trial period, 43% COBRA vs. 42% COBRA-light patients used prednisolone for ≥90 days, 34% vs. 44% patients switched to other DMARDs, and 39% vs. 28% patients used biologicals during the follow-up period. After mean 4 years follow-up, 49% COBRA vs. 47% COBRA-light patients had DAS<1.6, 50% vs. 48% had HAQ≤0.5, and 29% vs. 36% had SHS=0. Boolean remission occurred significantly more in the COBRA-light group (12% COBRA vs. 26% COBRA-light; p=0.04). Longitudinal data analyses showed equal effects of both COBRA and COBRA-light therapy on DAS, HAQ, SHS and Boolean remission over time. HAQ and SHS, both indicators of long-term efficacy, showed equal progression in both treatment groups during the 4 year follow-up period (Fig. 1 ). Conclusions: Early RA patients initially treated with COBRA or COBRA-light therapy showed similar outcome over a 4 year follow-up period. References: Den Uyl, ARD 2014, 73:1071–8; Ter Wee, ARD 2015, 74:1233–40 Disclosure of Interest: N. Konijn: None declared, L. van Tuyl: None declared, M. Boers Consultant for: MundiPharma, Pfizer, D. den Uijl: None declared, M. ter Wee: None declared, P. Kerstens: None declared, A. Voskuyl: None declared, D. van Schaardenburg: None declared, M. Nurmohamed: None declared, W. Lems Grant/research support from: This study was supported by an unrestricted grant from Pfizer